Early postoperative cognitive dysfunction after simultaneous coronary artery bypass grafting and carotid endarterectomy. (25th November 2020) - Maleva, O; Syrova, I; Trubnikova, O; Barbarash, O
Abstract: Purpose: To assess cognitive status after simultaneous coronary artery bypass grafting (CABG) and carotid endarterectomy (CEE). Material & methods. Changes in cognitive status and the incidence of POCD were evaluated in the early postoperative period after simultaneous CABG and CEE. 53 patients with polyvascular disease (PolyVD) undergoing CABG and CEE were included in the study. Patients were assigned to two groups. 25 patients without mild cognitive impairment (MCI), the mean age of 64.3±7.9 years, were included in Group 1 and 28 patients with MCI, the mean age of 65.3±6.75 years, were included in Group 2. Neuropsychological testing was performed on days 2 before surgery and on days 7 after surgery using the psycho-physiological testing software "Status PF". Attention was assessed with the Bourdon's test or proofreading test. Memory was estimated with the 10 numbers memorizing test, 10 words memorizing test, and 10 syllables memorizing test. The assessment of neurodynamics included the measurement of the complex visual-motor reaction time (VMRT), brain performance (BP), and functional mobility of the nervous processes (FMNP). The presence of POCD was estimated as a 20% decline on 20% of the tests. A reference range for neuropsychological indicators (13 indicators of the test battery) was set at the intervals corresponding to the ranges between the quartiles [Q25; Q75] in healthy people. Thus, cognitive status scale includes low cognitive status with the values ranging from 0 to 0.34, below the average - from 0.35 to 0.51, the average - from 0.52 to 0.7, and high cognitive status >0.7 to 1.0. Early postoperative cognitive dysfunction (POCD) was diagnosed as a 20% decline in memory, attention, and neurodynamics from the baseline on 20% of the tests passed. Statistical analysis was performed using the "Advanced" software package. Results: At baseline, cognitive status in patients without MCI was below the average (0.38±0.2), whereas in MCI patients it was lower by 32% and corresponded to low (0.26±0.1; p=0.03). Cognitive status did not differ significantly between both groups in the postoperative period, but a trend towards its decrease was determined (0.34±0.2 vs. 0.27±0.13, p>0.5). However, the incidence of early POCD in patients without MCI was 14 (56%), and in patients with MCI - 20 (71%) patients. Conclusion: At baseline, patients with PolyVD, regardless of the presence of MCI, according to the results of the comprehensive examination, showed low and below the average cognitive status. Simultaneous CABG and CEE does not prevent the deterioration of cognitive functions in patients with PolyVD in the early postoperative period. Patients with PolyVD undergoing myocardial and brain revascularization have a high risk of worsening cognitive disorders and need to individual approach to make a reasonable choice of the optimal surgical strategy. Funding Acknowledgement: Type of funding source: Public hospital(s). Main funding source(s): Institute